Spatial patterns of maternal mortality causes in West Kalimantan, Indonesia - Pertiwi, Tria Saras; Temesvari, Nauri Anggita; Nurmalasari, Mieke (Public Health of Indonesia, 2021)
Background: Maternal Mortality Rate (MMR) is one of the health indicators to see maternal survival in general and is a component in the health development index. Maternal Mortality Rate is also an important indicator of the quality of health services and the performance of the Health system.Objective: This study aimed to analyze the spatial patterns of maternal mortality based on the mortality causes in Sambas District, West Kalimantan, Indonesia.Methods: This study used a descriptive and exploratory approach to be able to see the distribution of maternal mortality and the coverage of the distribution of health care facilities. A spatial pattern was carried out to analyze the distribution pattern of maternal mortality cases using the Average Nearest Neighbor.Results: The results showed that most maternal mortality causes include bleeding, pregnancy hypertension, circulation system disorders (heart, stroke), metabolic disorders (diabetes mellitus), and other causes, such as pulmonary embolism. The analysis using a buffer of 3 kilometers and 5 kilometers show that not all the areas are covered by health service facilities in the Sambas district. Analysis of the mean of the nearest neighbors showed that the Nearest Neighbor ratio was 1.039398 with a z-score of 1.022396, which means that the pattern of distribution of maternal death according to the cause of death has a random pattern.Conclusion: The spatial pattern of cases of maternal death according to the cause of death in the Sambas district, West Kalimantan, Indonesia, has a random pattern. This finding can be used as a basis for decreasing the maternal mortality rate.